Autograph letter signed from Alexander Wheelock Thayer to George Fisher - Thayer, Alexander Wheelock, 1817-1897:::Creator::::::::::::; Fisher, George:::Contributor:::::::::::: (2021)
Autograph letter signed from Alexander Wheelock Thayer to George Fisher, from Trieste, Italy, dated Feb. 19, 1878, regarding the mailing of the Chronicle